2022
DOI: 10.1155/2022/1348795
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola rosea: A Therapeutic Candidate on Cardiovascular Diseases

Abstract: Cardiovascular diseases, also known as circulatory diseases, are diseases of the heart and blood vessels, and its etiology is hyperlipidemia, thick blood, atherosclerosis, and hypertension. Due to its high prevalence, disability, and mortality, it seriously threatens human health. According to reports, the incidence of cardiovascular disease is still on the rise. Rhodiola rosea is a kind of traditional Chinese medicine, which has the effects of antimyocardial ischemia-reperfusion injury, lowering blood fat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Rhodiola rosea contains approximately 140 constituents, including salidroside, tyrosol, rosavin, gallic acid, and rosaline [ 16 , 78 ]. Uyeturk et al have reported that Rhodiola rosea extract has preventive effects on testicular ischemia-reperfusion injury [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rhodiola rosea contains approximately 140 constituents, including salidroside, tyrosol, rosavin, gallic acid, and rosaline [ 16 , 78 ]. Uyeturk et al have reported that Rhodiola rosea extract has preventive effects on testicular ischemia-reperfusion injury [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other treatments with improved safety must be identi ed. Prior studies have demonstrated that Chinese herbal medicines have great advantages in the treatment of diabetes [40][41][42], in ammation [43], nervous system diseases [19,[44][45], cancer [46-48], COVID-19 [46], and cardiovascular diseases [50]. Therefore, we turned our attention to Chinese herbal medicines and their prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…It participates in the hydrolysis of lipid peroxide by scavenging free radicals to protect cells from lipid peroxide accumulation [16]. Prior studies [17][18][19][20] have also reported that traditional Chinese medicine has obvious advantages in the treatment of cardiovascular disease, which can improve the prognosis of patients, reduce the incidence of complications, and improve the safety of the medication. The representative compound preparation for the clinical treatment of CS in China is Shenfu injection (SFI).…”
Section: Introductionmentioning
confidence: 99%
“…should be treated as a synonym of R. rosea L., the most reputed species of the Rhodiola genus. Botanical description of the plant as well as information on its distribution, ethnobotany, and medicinal properties is easy to find in the literature [ 65 , 91 , 92 ]. In one study, the HRs of R. sachalinensis were obtained via the infection of leaf explants with R. rhizogenes strain A4.…”
Section: Phenolic and Polyphenolic Antioxidants In Hrsmentioning
confidence: 99%